Strategic Thinking in Advertising. A Multidisciplinary Perspective - Muñoz-Sánchez, Omar; Vélez-Ochoa, Claudia Inés (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2020)
This article seeks to identify the contribution of other disciplines in the work of the account planner in the development of advertising communication strategies, and attempts to answer the question: what sources of knowledge influence the way of thinking of the advertising account planner? For the above, qualitative research of exploratory kind is proposed, in which a bibliographic trace of in-depth interviews to 21 account planners is done in the cities of Bogota, Medellin and Cali. One of the most significant findings is the relevance of account planners undertaking postgraduate studies that allow them to access knowledge from other disciplines so that they can holistically understand the consumer. It was found that this highly creative advertising professional emerged in Colombia empirically, and only from 2006, it is being worked on the construction of the respective epistemology.